NEW CONTRIBUTIONS TO THE KNOWLEDGE OF LEPIDORTERA FAUNA OF KOSOVO AND METOHIA (REPUBLIC OF SERBIA) - Jakšić, Predrag (Bulletin of Natural Sciences Research, 2016)
Seven species of Lepidoptera – Triodia sylvina (Linnaeus, 1761), Trichiura crataegi (Linnaeus, 1758), Eriogaster lanestris (Linnaeus, 1758), Endromis versicolora (Linnaeus, 1758), Caradrina clavipalpis (Scopoli, 1763), Polymixis rufocincta (Gayer, 1828) and Oria musculosa (Hübner, 1808) were recorded for the first time in Kosovo and Metohia, Republic of Serbia. The next seven species- Trichiura crataegi (Linnaues, 1758), Lycia graecarius (Staudinger, 1861), Biston strataria (Hufnagel, 1767), Agriopis aurantiaria (Hübner, 1799), Erannis defoliaria (Clerck, 1759), Parasemia plantaginis (Linnaeus, 1758) and Euplagia quadripunctaria (Poda, 1761) were confirmed for the same area. Besides detailed faunistic data, illustrations of some adults are given.